Pengaruh Penggunaan Aplikasi Kahoot! terhadap Minat Belajar Siswa pada Mata Pelajaran Sejarah Kebudayaan Islam (SKI) di MAN 1 Kota Bogor - Handayani, Dewi; Lisnawati, Santi; Abristadevi, Abristadevi (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the low interest in learning among students in the subject of Islamic Cultural History, despite the fact that this phenomenon has a significant impact on education. The purpose of this research is to investigate the effect of the Kahoot! application on student interest in the subject of Islamic Cultural History (Sejarah Kebudayaan Islam, SKI) in the twelfth grade at Madrasah Aliyah Negeri 1 Kota Bogor. The method used is quantitative with a quasi-experimental approach and a non-equivalent design, with a sample of 60 students selected through purposive sampling. Data were collected using a learning interest questionnaire instrument designed to measure student engagement, interest, attention, and enjoyment, and were analyzed using an independent sample t-test. The results indicate that there is a significant effect of the Kahoot! application on student interest in the SKI subject for twelfth grade at MAN 1 Kota Bogor. The main conclusion of this study is that the analysis results from the independent sample t-test using SPSS 26.0 show that Kahoot! is an effective interactive learning tool for increasing student interest, evidenced by higher evaluation scores in the experimental class. Therefore, Kahoot! is recommended as an alternative for teaching SKI as it creates a fun and engaging learning environment. The implications of this research encompass theoretical aspects, where this study contributes to strengthening the theory regarding the importance of interactive learning media in enhancing student interest, as well as practical aspects for teachers, where the use of Kahoot! can be a fun teaching strategy that improves student engagement in the classroom. These findings can serve as a basis for schools or educational institutions to integrate interactive digital media into the curriculum, especially in technology-based learning.